Practical Analysis of Video Tutorials in Learning the Use of Electric Skin Care Equipment - Zulfiani, Putri Chairina; Ratri, Pramesti Adika; Putri, Mutia; Atika, Liana; Sari, Dian Maya; Putri, Wisri Ardhita Manda (Universitas Negeri Semarang, 2025)
The development of education today is marked by rapid technological innovation. This requires adjustments to the education system to keep in line with the needs of the workplace, which is also constantly changing due to technology. In other words, education needs to adapt so that graduates have skills that are relevant to the existing job market. The selection and use of learning media must be in line with the rapid advances in science and technology. Therefore, lecturers are expected to utilize information and communication technology to support the teaching and learning process, so that learning becomes more effective. The Cosmetology Education Study Program, as one of the study programs at State University of Medan, has a vision to become a superior study program in the field of vocational education, mastering technology, industrial engineering, and culture, in line with the field of cosmetology. To facilitate students in learning the material, the author created a digital learning medium in the form of a video tutorial on the use of electric facial care tools in the electric skin care subject in the Cosmetology Education Study Program, Faculty of Engineering, Medan State University. Therefore, this study aims to describe the practicality of video tutorials. This study is a quantitative descriptive study with data collection using questionnaires. The respondents in this study were 35 students majoring in Cosmetology who took the Electric Skin Care course in the odd semester from August to December 2024. The results of the study indicate that the tutorial videos used in the lectures were categorized as very practical with a score percentage of 42%; practical with a score percentage of 50%; and 8% were categorized as sufficient practical.